ANALISIS KEPUASAN KONSUMEN CAFE SHOP COFFINE COFFE DI KOTA TEBING TINGGI, SUMATRA UTARA - Cang, Vincent Clarence; Doloksaribu, Winda Sri Astuti; Wicharta, Jeffrie; Nahrisah, Ezzah (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to examine the effect of service quality, product quality, and price on consumer satisfaction. The data analysis method used includes the F-test and T-test to determine the relationship and significance of each variable. The analysis results show that service quality has a positive effect on consumer satisfaction, with an F-test value of 0.837 > 0.662, a t-statistic of 2.345 > 1.96, and a p-value of 0.006 < 0.05, thus supporting the first hypothesis (H1). Furthermore, the effect of product quality on consumer satisfaction is also significant, with an F-test value of 0.829 > 0.662, a t-statistic of 2.911 > 1.96, and a p-value of 0.004 < 0.05, confirming the second hypothesis (H2). The price variable also positively influences consumer satisfaction, as indicated by an NFI value of 0.829 > 0.662, a t-statistic of 5.562 > 1.96, and a p-value of 0.000 < 0.05, supporting the third hypothesis (H3). Simultaneously, service quality, product quality, and price have a positive effect on consumer satisfaction, as shown by the analysis results confirming the acceptance of H1, H2, and H3 based on the T-test criteria. This study provides insights that improving service quality, product quality, and effective price management can significantly enhance consumer satisfaction.